Synthesis, Thermal and Spectral Studies of Mn(II), Co(II), Cu(II) and Zn(II) Complexes of Cinnamaldehydeanthranilic Acid - Sleema, B.; Parameswaran, Geetha (Asian Journal of Chemistry, 2010)
Complexes of Mn(II), Co(II), Cu(II) and Zn(II) with Schiff base formed by condensation of cinnamaldehyde and anthranilic acid have been synthesized and their physicochemical properties have been investigated by elemental analysis, magnetic measurement, molar conductance, electronic spectroscopy, infrared spectroscopy and thermal studies. The ligand was found to be bidentate chelating agent for the metal ions. Thermal decomposition data of the complexes have been analyzed to obtain the activation energy, entropy of activation and frequency factor based on Coats-Redfern equation. The relative thermal stability of the chelates can be given as [MnLOAc(H2O)3] ≈ [ZnLOAc(H2O)] < [CoLOAc(H2O)3] < [CuLOAc(H2O)].